Opioid use disorder in pregnancy: leveraging provider perceptions to inform comprehensive treatment - Doris Titus-Glover; Fadia T. Shaya; Christopher Welsh; Danya M. Qato; Savyasachi Shah; Laura E. Gresssler; Rebecca Vivrette (BMC, 2021)
Abstract Background Medications for opioid use disorder (MOUD) are recommended with adjuvant behavioral therapies, counseling, and other services for comprehensive treatment of maternal opioid use disorder. Inadequate access to treatment, lack of prescribing providers and complex delivery models are among known barriers to care. Multi-disciplinary provider input can be leveraged to comprehend factors that facilitate or inhibit treatment. The objective of this study is to explore provider perceptions of MOUD and factors critical to comprehensive treatment delivery to improve the care of pregnant women with opioid use disorder. Methods A qualitative research approach was used to gather data from individual provider and group semi-structured interviews. Providers (n = 12) responded to questions in several domains related to perceptions of MOUD, treatment delivery, access to resources, and challenges/barriers. Data were collected, transcribed, coded (by consensus) and emerging themes were analyzed using grounded theory methodology. Results Emerging themes revealed persistent gaps in treatment and challenges in provider, health systems and patient factors. Providers perceived MOUD to be a "lifeline" to women. Conclusions Inconsistencies in treatment provision, access and uptake can be improved by leveraging provider perceptions, direct experiences and recommendations for an integrated team-based, patient-centered approach to guide the care of pregnant women with opioid use disorder.